The viability and appropriateness of using visual methods in end of life research to foreground the experiences of people affected by financial hardship and deprivation. (April 2023) - Richards, Naomi; Quinn, Sam; Mitchell, Margaret; Carduff, Emma; Gott, Merryn
Background: Visual methods have been used extensively in social research to explore people's experiences of structural disadvantage. This indicates that they may provide a useful research approach to understanding equity-related concerns within palliative care. However, little has been published regarding the use of visual methods with people at the end of life. Purpose of the paper: In this article we draw on our experiences of using visual methods to illuminate the end of life experiences of people experiencing financial hardship and deprivation in Scotland's largest city. Evidence used to support the information presented: We present evidence from the published literature, as well as our own experiences of using visual methods to explore dying at home for people experiencing financial hardship and deprivation. Our analysis draws on two specific visual methods: photovoice and professional photography. Photovoice is a participatory visual method which involves enabling participants to take and discuss their own images and present them to different audiences to try to enact social change. We report our experiences as researchers, as well as those of our participants and recruitment partners. Key learning points: To successfully use visual methods, researchers need to invest significant time and resource in building a strong rapport with participants. There are also key ethical, practical and representational challenges to consider. A participatory framework should be adopted which ensures agency for participants in terms of image creation and public dissemination. Participants reported value in using visual methods in terms of legacy building and self-representation. Using photovoice (insider's view) and professional photography (outsider's view) together offered complementary perspectives, enabling a rich layering of stories and meaning. Our findings indicate visual methods can illuminate aspects of the end of life experience not captured by other research methods.